Privileging wage and salary increases? Who asks, gets, doesn't ask or doesn't get a raise in Australia. (2nd July 2020) - Cebulla, Andreas
ABSTRACT: Australian workers have experienced low to no wage growth for several years. This study examines Australian Workplace Relations Study data to describe and categorise workers' experiences in obtaining wage or salary increases, or a promotion, in their current workplaces. The findings suggest sharp divisions. On one hand, there are those achieving better pay and/or promotions who include managers, but also clerical and administrative workers, who often also benefit from bonus payments or commissions; and workers in companies covered largely by Individual Arrangements who negotiate their wages. These groups contrast with workers without pay rise or promotion, who include community and personal service workers, some of whom opt not to seek better conditions. One worker in eight is tied to a firm without processes and procedures for promotion or wage negotiations, and without recent experience of improved conditions.